KEABSAHAN PRAKTIK AKAD NIKAH ORANG ISLAM DENGAN MASYARAKAT ADAT SAMIN DI DESA KARANGROWO UNDAAN KABUPATEN KUDUS - Azzulfa, Fatihatul Anhar; Nafis, Moh Durrul Ainun (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2022)
The study aims to determine the practice of the Samin customary marriage contract with Muslims (non Samin) in Karangrowoi Village, Undaani district, Kudus Regency hich has differences with the marriage contract procession in general, where between ijab and kabul there must be a grace period (separately). The method used is descriptive-qualitative, which describe and explore the practice of marriage contract in the Samin community and then analyzes it based on the perspective of Islamic law and positif law. This tudy found that, what should have been the implementation of ijab and kabul carried out in one assembly (in one space and time), isn’t done that way by indigenous people of Samin. The implementation, kabul is delivered at different times so that its validity isn’t fulfilled as required by the pillars and conditions of marriage.